Externalities and sustainable agri-food system - Henry Inegbedion (Discover Food)
Abstract The study investigated the influence of externalities on sustainable agri-food systems. The purpose was to find out the extent to which the inclusion of the cost of externalities in the price of food will translate to a more sustainable agricultural food system. The study used the cross-sectional survey design consisting of 216 randomly selected farmers of agri-food, in south-south Nigeria. A structured questionnaire served as the instrument of data collection. Convergent and divergent validity tests served to test for validity of the questionnaire while composite reliability tests served the purpose of testing for reliability. The study employed path diagram analysis using the structural equation modelling technique to test for the significance of data. The results indicate that the various costs of externalities (environmental, social, health and economic) have statistically significant relationships with agri-food sustainability. The study recommends including the cost of externalities in food pricing facilitating the drive towards a sustainable food system. The study makes a significant contribution to empirical and theoretical literature.